2021
DOI: 10.1186/s12978-021-01167-y
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety among pregnant mothers in the initial stage of the Coronavirus Disease (COVID-19) pandemic in the southwest of Iran

Abstract: ‌Background Women are at a higher risk for depression progression, especially during pregnancy. The current study purposed to investigate depression, anxiety, and stress levels of pregnant mothers in the initial stage of the COVID-19 infection in the southwest of Iran. Methods This cross-sectional study was conducted during March and April, 2020, in Shiraz, Iran. Pregnant mothers registered in maternity clinics affiliated with Shiraz University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
2
17
3
Order By: Relevance
“…Education is an important factor related to the development of anxiety and depression during pregnancy. Although our results only found higher risk of depression in pregnant women with low education levels, pregnant women with low education levels have been reported to be a high risk of developing both anxiety and depressive symptoms [8,37]. This may be explained…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Education is an important factor related to the development of anxiety and depression during pregnancy. Although our results only found higher risk of depression in pregnant women with low education levels, pregnant women with low education levels have been reported to be a high risk of developing both anxiety and depressive symptoms [8,37]. This may be explained…”
Section: Discussioncontrasting
confidence: 75%
“…Of the ten excluded studies, two papers were reviews, seven papers lacked enough data, and one paper was excluded with duplicated data [22] and the updated data were included [23]. Finally, 17 studies [1,8,12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] met the inclusion criteria for this study, including 15,050 pregnant women during the COVID-19 pandemic. The details in selected studies were listed in Table 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ayaz et al carried out a study in Turkey during the COVID-19 pandemic period, and it was reported that the depression levels of pregnant women are above the moderate level (Ayaz et al, 2020 ). Maharlouei et al reported that the depression levels of pregnant women in Iran were above the moderate level (Maharlouei et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%